New Partners for the Planet? The European Union and China in International Climate Governance from a Role-Theoretical Perspective - Julia Gurol; Anna Starkmann (JCMS: Journal of Common Market Studies, 2021)
Only with the three largest emitters (the EU, China and the US) building a coalition was it possible to conclude the Paris Agreement in 2015. With the announced withdrawal of the US, the interdependence between the EU and China has increased significantly. Both actors have reiterated their will to implement the Paris Agreement and to cooperate on climate change. In times of political constraints between the EU and China, this seems puzzling. The paper takes a role-theoretic perspective to assess the following question: How can the changing roles of the EU and China, ascribed to them by external and internal expectations, explain their increased climate cooperation? It draws on a qualitative text analysis of policy documents and expert interviews. The paper concludes with a discussion of the findings against the backdrop of growing tensions between the EU and China.
Keywords: 330; European Union; China; role theory; cooperation; climate change